2015
DOI: 10.1089/jmf.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt Containing the ProbacteriaLactobacillus acidophilusCombined with Natural Antioxidants Mitigates Doxorubicin-Induced Cardiomyopathy in Rats

Abstract: Probiotics and antioxidants have a definite improving effect in cardiovascular diseases. This study aims at mitigating doxorubicin toxicity on cardiac function through consuming a functional food. Five groups of adult male Sprague-Dawley rats were used along 22 weeks. Group I received 30 g/kg/day food enriched with yogurt, green tea extract, and carrots (80, 0.84, and 100 g/kg diet, respectively) from the first week, group II received carvedilol 30 mg/kg/day orally from week 17, group III received both carvedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Reducing lipid peroxidation and protecting the liver from oxidative effects of free radicals will be one of the main strategies to promote conversion of T4 to T3 by using herbs (Sage, 2013). Meanwhile L. acidophilus proved its effectiveness as antioxidant (Abu-Elsaad et al, 2015) this has resulted in appositive way to increase the conversion of T4 to T3 in the present experiment. Same results recorded by (Chenhui et al, 2014) who found that feeding Se-probiotics caused increase in T3 and not T4.…”
Section: Ne Usmentioning
confidence: 50%
“…Reducing lipid peroxidation and protecting the liver from oxidative effects of free radicals will be one of the main strategies to promote conversion of T4 to T3 by using herbs (Sage, 2013). Meanwhile L. acidophilus proved its effectiveness as antioxidant (Abu-Elsaad et al, 2015) this has resulted in appositive way to increase the conversion of T4 to T3 in the present experiment. Same results recorded by (Chenhui et al, 2014) who found that feeding Se-probiotics caused increase in T3 and not T4.…”
Section: Ne Usmentioning
confidence: 50%
“…H9c2 cells were incubated with the same concentration of doxorubicin and subsequently cotreated with various concentrations of curcumin for 2 h. At the end of the treatment, the cells were harvested and sonicated with phosphate buffer (PBS, pH 6.8) containing 1 mmol phenylmethanesulfonyl fluoride (PMSF) to obtain cell homogenates. The thiobarbituric acid-reactive substances (TBARS) method was used to estimate the cellular malondialdehyde (MDA) levels by measuring the absorbance at 532 nm with a spectrophotometer [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Probiotic food comprising yogurt, green tea extract and carrots improved membrane integrity and cardiac contractility in doxorubicin-induced cardiomyopathy. 1 Tea drinking was significantly associated with lower overall cancer and cardiovascular mortality in men, but demonstrated no association with mortality in women. 2 The combination of yogurt and green tea in the preventions of heart disease and cancer has not been well documented.…”
mentioning
confidence: 91%